4C.06: COGNITIVE STATUS IN HYPERTENSIVE PATIENTS. HEART AND BRAIN STUDY IN ARGENTINE. (June 2015) - Cerezo, G.H.; Del Sueldo, M.; Zilberman, J.; Pawluk, M.; Lodolo, N.; De Cerchio, A.E.; Ruffa, R.M.; Plunket, R.; Giuliano, M.E.; Forcada, P.; Hauad, S.; Flores, R.; et al.
Abstract : Objective: Know the cognitive status of hypertensive patients, the prevalence of the cognitive impairment and its association with different parameters of hypertensive disease. Design and method: Multicenter study (18 centers) distributed in 5 regions of the Argentine. Epidemiological, cross and observational study. In the Heart and Brain Study, 1281 hypertensive patients, >/ = 21 years, both sexes were included. The sample was obtained by patients attending cardiology clinic. A validated survey with closed answers was used. Blood pressure (BP) was obtained according to international norms. The hypertensives patients were divided in two groups: treated/controlled (</ = 140 and </ = 90 mm Hg) and treated/no-controlled (>140 y >90 mm Hg). The education levels was registered. Cognition was assessed by Mini-Mental Statement Examination (MMSE) (global cognition), Clock drawing test (executive function), mini-Boston Naming Test (mBNT)(semantic memory). The cut-off of the test were: 1) MMSE </ = 24 pts., CDT </ = 5 pts., mBNT </ = 9 pts. (applied in patients >/ = 60 years with >/ = 7 years education). Results: Average age was 60, 2 ± 13, 5 yrs, 71% female (n = 881). In the treated /controlled group (n = 570; 46, 0%) the BP (SBP 125.8 ± 9.7 mm Hg and DBP 75.9 ± 8.4 mm Hg) was lower than treated/no-controlled group (SBP 155.5 ± 18.4 mm Hg and DBP 88.7 ± 11.6 mm Hg) (p <0.001). In the treated/no-controlled group, higher OR for poor outcomes in mini-BNT was observed (OR = 1.36; CI 95%, 1.04–1.75, p = 0.021), ajusting for age, sex and education level in the logistic regression model. The 22.1% presented impairment in global cognition, 36.2% executive dysfunction and 48.9% impairment semantic memory. In the one way analysis of variance, high pulse pressure was associated with poor outcomes in CDT (<0.0036) and mini-BNT (<0.001), whereas that SBP was associated with poor outcomes in mini-BNT (<0.001). But, after ajusting (age, sex, education) in the linear regression model the miniBNT was the only test associated with high BP (p 0.05). Conclusions: In this sample of hypertensive patients impairment of the semantic memory (cortical function) was more prevalent than executive dysfunction (sub-cortical). The miniBNT was the only test associated with high BP in treated/no-controlled group. Hypertension could impact negatively on cortical structures as well as the known subcortical.